In vivo proximity-labeling with miniTurboID to screen for protein-protein interactions in the filamentous ascomycete Sordaria macrospora - Lucas S. Hollstein; Svenja Groth; Kerstin Schmitt; Oliver Valerius; Stefanie Pöggeler (MethodsX)
The Biotin Identification (BioID) method applies proximity-dependent labeling of co-localizing proteins to screen for protein-protein interactions in vivo. Therefore, the protein of interest (POI) is fused to a promiscuous biotin ligase. This ligase covalently biotinylates proximal proteins, which allows their specific enrichment and subsequent identification by mass spectrometry. In recent research, the BioID method was applied in the filamentous ascomycete Sordaria macrospora using a codon optimized TurboID ligase. In this study, we applied a smaller variant of the TurboID biotin ligase, named miniTurboID to perform BioID experiments in S. macrospora. Here, we provide a comprehensive and detailed guideline of experimental steps for the application of BioID in filamentous fungi. • The BioID method screens for protein-protein interactions via in vivo labeling of nearby proteins through a biotin ligase, which is fused to the POI • TurboID and miniTurboID ligases can be used for BioID experiments in the filamentous fungus Sordaria macrospora